A Study of Arabic Language Linguistic and Stylistic Patterns of Conditional Constraints and their Rhetorical Significance - Khan, Habibullah; al Rashidi, Muhammad Ayub (Journal of Islamic and Religious Studies, 2020)
This research deals with conditional constraints and their impact on determining a useful meaning. Conditional constraints in the sentence have a major impact in determining the meaning and highlighting its features. The connotations of the structures vary with these constraints, even if they are agreed upon in the two basic pillars, i.e Musnad and Musnad ilayhi, as the structure with the constraint results in a useful meaningful, which cannot be delivered without it. This study intends to draw out different aspects of meanings clauses such as five Mafā‘īls, Ḥāl, Tamyīz, Istithnā‘, Tawābi’, Sharṭ and Af’āl Nāqiṣah in connection with conditional constraints. It describes all of them along with their rhetoric perspectives theoretically and empirically. There are many views of rhetoric scholars. The aforementioned linguistic patterns are going to be examined specifically following the attempt made by Imām ‘Abd Qāhir al Jurjānī in his magnificent work entitled “Dalā’il al-I’jāz” as well as other dominant views in this conspicuous regard. The study concluded that the constraints in the composition are required by the structure of meaning. With these clauses, the structures are distinguished, and their degree of eloquence varies. If the constraints were dropped, the rhetoric would be absent. The advantage of speech and its high degree is only with the constraints around it.